Evaluation of Groundwater Potential Zones in Sg. Seguntor, Sandakan, Sabah, Malaysia by using the Geographical Information System (GIS) Method - Zulherry Isnain; Muhammad Shazali Azahar (Technoscience Publications, 2025)
This study was conducted to determine the groundwater potential zone by using the Geographical Information System (GIS) method in Sungai Seguntor, Sandakan, Sabah, Malaysia, and its surroundings. The study area consists of Sandakan Formation, Volcanic Breccia and Quaternary Alluvium. The ArcGIS 10.5 and Global Mapper software was used in this study. Eight thematic maps have been produced; lithological map, rainfall map, drainage density map, lineament density map, soil type map, landuse map, elevation map and slope steepness map. GIS methods were used during the spatial analysis stage. All the thematic maps are weighted based on their emphasis on the existence of groundwater. During the map integration stage, the Raster Calculator is used based on the Eigen Vector of each parameter. The final map produced shows that almost 30% of the study area has high groundwater potential, most of which are in lowland alluvium areas with relatively high drainage density. This final map also shows significant results with tube well data obtained from the Department of Minerals and Geosciences, Sabah, Malaysia.